Efficient Algorithm for Solving Fuzzy Singularly Perturbed Volterra Integro-Differential Equation - Al-Abrahemee, Khalid Mindeel Mohammed (Iraqi Journal of Science, 2023)
In this paper, we design a fuzzy neural network to solve fuzzy singularly perturbed Volterra integro-differential equation by using a High Performance Training Algorithm such as the Levenberge-Marqaurdt (TrianLM) and the sigmoid function of the hidden units which is the hyperbolic tangent activation function. A fuzzy trial solution to fuzzy singularly perturbed Volterra integro-differential equation is written as a sum of two components. The first component meets the fuzzy requirements, however, it does not have any fuzzy adjustable parameters. The second component is a feed-forward fuzzy neural network with fuzzy adjustable parameters. The proposed method is compared with the analytical solutions. We find that the proposed method has excellent accuracy in findings, a lower error rate, and faster convergence than other typical methods.